O-002 Solitaire FR revascularization device: a European retrospective study as a first line device for acute ischemic stroke. (12th July 2011) - Mendes pereira, V; Gralla, J; Bonafe, A; Chapot, R; Anderson, T; Castano, C
Abstract : Retrospective data collection from European sites experienced with the use of the Solitaire FR, when used as 1st choice device to treat patients with ischemic stroke and restore blood flow. Six European centers treated 141 patients for acute ischemic stroke using the Solitaire FR, as first intention device, in relation to their own clinical practice which involved the use of mechanical thrombectomy devices and pharmacologic agents from March 2009 to June 2010. The centers involved were Germans Trias Hospital in Barcelona, Geneva University Hospital, Inselspital University Hospital of Bern, Hôpital Gui de Chauliac in Montpellier, Karolinska sjukhuset in Stockholm, AKK Hospital in Essen.Of the 141 patients, 44% were female and 89% of the occlusions were in the anterior anatomy. The median baseline NIHSS score was 18. The revascularization success (TICI≥2b) was 89.4%. The median procedure time from groin puncture to revascularization was 45 min. Good Clinical Outcome (mRS ≤2) at 90 days was 54.6%.